Extralobar pulmonary sequestration in an adult male with a heart defect. Case report - Andrey M. Makarevich; Andrey A. Zaytsev; Elena M. Makarevich; Hasan A. Akhmedkhanov (ZAO "Consilium Medicum", 2024)
Pulmonary sequestration (PS) is a rare congenital malformation of the lungs referring to an abnormal (non-functioning) segment of the lung that has no connection with the tracheobronchial tree, which receives arterial blood from systemic circulation and has various types of venous outflow. PS is divided into intralobar (intrapulmonary) and extralobar (extrapulmonary) types. The distinctive feature of extralobar pulmonary sequestration is the presence of its own visceral pleura. PS is most common in pediatric practice; in some cases, this disease may remain oligosymptomatic or asymptomatic in children and adolescents. Adults with PS have a higher risk of recurrent pneumonia, chest pain, and episodes of hemoptysis. Cases of the late onset of PS are reported in a few foreign and Russian publications. The special feature was the elderly patients with a long asymptomatic course of PS, "pseudopneumonic" clinical onset, episodes of thoracalgia and hemoptysis. We present a case of an adult male soldier with PS clinically simulated a respiratory infection in the lower lobe of the left lung with severe pain and hemoptysis. In addition, the patient has a concomitant congenital heart defect.